Adoption of Cryptocurrencies as a Means of Exchange - Hern, Chong Zhao; Zakaria , Nadisah; Sulaiman, Ainin; Min , Foo Siong; Kamaludin, Kamilah (Journal of Ecohumanism, 2024)
This study examines the determinants impacting the adoption of cryptocurrencies for exchange. Through a quantitative approach, data from 104 respondents were gathered via an internet-based survey. Employing a Likert scale, the study examined the relationship between financial literacy, perceived usefulness, perceived ease of use, and willingness to adopt cryptocurrencies. Results revealed that financial literacy did not directly correlate with the willingness to adopt cryptocurrencies, while perceived usefulness and ease of use exhibited a positive association with adoption. Notably, the present study highlighted the reliance on perceived financial literacy rather than actual levels. It emphasized the necessity of improving the accessibility and applicability of cryptocurrencies to encourage their adoption. The implications of this study are pertinent to policymakers and businesses venturing into cryptocurrency integration. Understanding the influencers of cryptocurrency adoption, especially perceived utility and ease of use, can inform strategic approaches to foster adoption of cryptocurrencies.